El camino hacia la sostenibilidad en el País Vasco. La Agenda 21 en Vitoria-Gasteiz - Galdós Urrutia, R.; Ruiz Urrestarazu, E. (Geographicalia, 2016)
The article deals with actions carried out by the Department of Environment and Regional Planning for the Basque Government in order to suppost the introduction of Local Agenda 21 in Basque municipalities. Special emphasis is placed on networking via intermunicipal cooperation. By way of acase study, the municipal area of Vitoria-Gasteiz -pioneer in the region for implementing the said Local Agenda 21- has been chosen, providing an opportunityt o make an initial assessment of its achievements and failures.
Keywords: Local Agenda 21; Sustainability Indicators; Basque Country; Vitoria- Gasteiz